Mister Exam

Other calculators


(7x+1)-(9x+3)=5

(7x+1)-(9x+3)=5 equation

The teacher will be very surprised to see your correct solution 😉

v

Numerical solution:

Do search numerical solution at [, ]

The solution

You have entered [src]
7*x + 1 + -9*x - 3 = 5
(9x3)+(7x+1)=5\left(- 9 x - 3\right) + \left(7 x + 1\right) = 5
Detail solution
Given the linear equation:
(7*x+1)-(9*x+3) = 5

Expand brackets in the left part
7*x+1-9*x-3 = 5

Looking for similar summands in the left part:
-2 - 2*x = 5

Move free summands (without x)
from left part to right part, we given:
2x=7- 2 x = 7
Divide both parts of the equation by -2
x = 7 / (-2)

We get the answer: x = -7/2
The graph
-20.0-17.5-15.0-12.5-10.0-7.5-5.0-2.50.02.55.07.5-5050
Sum and product of roots [src]
sum
-7/2
72- \frac{7}{2}
=
-7/2
72- \frac{7}{2}
product
-7/2
72- \frac{7}{2}
=
-7/2
72- \frac{7}{2}
-7/2
Rapid solution [src]
x1 = -7/2
x1=72x_{1} = - \frac{7}{2}
x1 = -7/2
Numerical answer [src]
x1 = -3.5
x1 = -3.5
The graph
(7x+1)-(9x+3)=5 equation